Translation of Indonesian-Arabic Food Product Terms to Enhance Students’ Vocabulary - Yafiatul, Azzah Fatin; Fahmi, Kaula; Mubarok, M. Zacky; Anas, Muammad; Suparno, Darsita; Fathalah, Fathalah Muhamed (Universitas Muhammadiyah Sumatera Barat, 2025)
Translation of food product labels has become very important along with the current export-import activities. However, the translation of product labels has become a language and cultural issue. Translators are one indicator of the occurrence of this issue. This study aims to identify translation techniques used on the product labels of one of the snack companies in Indonesia, PT Manohara Asri. This research method uses a descriptive qualitative approach by collecting data samples in the form of snack packaging, then producing description data in the form of written data related to translation techniques used by translators. The results of the study found that there were 7 translation techniques used, namely, literal techniques, transposition techniques, lending techniques, amplification techniques, description techniques, modulation techniques, and particulation techniques. Of the 48 data found in 7 product packaging, it shows that the literal translation technique is the most common technique found on the product label. This research can be used as reference and improvement material for PT Manohara Asri and can be a knowledge for the wider community.